Peran Celebrity Endorsment, Kontrol Diri dan Literasi Ekonomi Terhadap Perilaku Belanja Implusive Generasi Z pada Platform Digital: Studi Mahasiswa Semester Rendah Universitas Dian Nuswantoro Semarang - Insanul Syakiroh; Rudi Kurniawan; Suhita Whini Setyahuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the influence of celebrity endorsement, self-control, and economic literacy on impulsive buying behavior among Generation Z university students on digital platforms. The novelty of this research lies in the combination of these three variables tested simultaneously, as previous studies have generally focused on only one or two variables separately. The population of this study includes all active students of Universitas Dian Nuswantoro Semarang. The sampling technique used is purposive sampling, with the criteria that respondents are early-semester students (semester 1 and 3), actively use social media and e-commerce platforms, and have experience in making online purchases. The total sample size in this study is 157 respondents. Data were collected through a questionnaire based on a Likert scale and analyzed using the Partial Least Square (PLS) approach to examine the relationships between variables. The results show that all three variables—celebrity endorsement, self-control, and economic literacy—have a significant effect on impulsive buying behavior. Among them, celebrity endorsement has the strongest influence in driving spontaneous purchasing decisions. This study highlights that both social influence and individuals’ ability to control themselves, along with their understanding of economic concepts, play a crucial role in shaping students’ consumption behavior in the digital era.